Effect of Perinatal Outcomes on the Stage of Primary Dentition Eruption - Yassin, Heba N (Scripta Medica, 2025)
Background/Aim: Understanding how perinatal outcome variations affect dentition eruption can lead to healthcare providers monitoring and managing dental health in infants and children. This study aimed to evaluate the influence of gestational age, mode of delivery and birth weight on the stage of primary dentition eruption in children. Methods: A sample of 304 children aged 6-24 months from Baghdad city was studied. Information about gestational age, delivery method (vaginal vs Caesarean) and birth weight were evaluated through a parent- answered sheet. The stage of dental eruption was estimated based on the criteria established by Damodar P Swami. Statistical and descriptive analyses were utilised to compare the dental eruption stages across different groups. Results: Most of the study population (62.8 %) exhibited eruption stage 3 and statistical analysis revealed no significant differences in eruption stage when compared across variable groups, including gestational age, delivery method and birth weight. Conclusion: Results indicate the possible early effects of birth weight during eruption of deciduous teeth in young infants (6-11 months). This potential effect appears to decrease with age and was not statistically significant in older age. In contrast, gestational age and mode of delivery showed no significant effects on the stage of deciduous teeth eruption. These results provide valuable insights to paediatric dentists.